Lecture09 - Lecture 9 Recall: L = [ a,b ] ⊂ U F → Y F...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Lecture 9 Recall: L = [ a,b ] ⊂ U F → Y F differentiable at each point of L Ψ ∈ Y * ⇒ ∃ p ∈ L such that Ψ( F ( b )- F ( a )) = Ψ( F p ( b- a )) Theorem 1 (MVT) . If F : U → Y is differentiable at each point of [ a,b ] ⊂ U then there exists p ∈ ( a,b ) such that k F ( b )- F ( a ) k ≤ k F p ( b- a ) k ( ≤ k F p kk b- a k ) Proof. Let Ψ ∈ Y * be such that k Ψ k = 1 and Ψ( F ( b )- F ( a )) = k F ( b )- F ( a ) k . Apply previous MVT: there exists p ∈ ( a,b ) such that k F ( b )- F ( a ) k = Ψ( F ( b )- F ( a )) = Ψ( F p ( b- a )) ≤ k Ψ kk F p ( b- a ) k = k F p ( b- a ) k ( k Ψ k = 1) . Theorem 2 (MVT) . Let F : U → Y be differentiable and [ a,b ] ⊂ U . If p ∈ U then k F ( b )- F ( a )- F p ( b- a ) k ≤ k b- a k sup q ∈ [ a,b ] k F q- F p k . 1 Proof. Apply the previous MVT to G : U → Y : x 7→ F ( x )- F p ( x ) . G is differentiable at each q ∈ U and G q ( h ) = F q ( h )- F p ( h ) ....
View Full Document

This note was uploaded on 07/08/2011 for the course MAT 6932 taught by Professor Staff during the Summer '10 term at University of Florida.

Page1 / 4

Lecture09 - Lecture 9 Recall: L = [ a,b ] ⊂ U F → Y F...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online